Application of the Analytical Hierarchy Process (AHP) Method in Hospitality Waiters Recruitment - Preddy Marpaung; Rita Hamdani (INFOKUM, 2021)
Hospitality waiters are the spearhead of a hotel in providing services to guests or customers. Where also the dignity of a hotel is in the waiters themselves, because it is the waiters who deal directly with customers such as welcoming guests, providing information about hotels, honesty, behavior and other matters related to service. Therefore, it is necessary to pay attention to the criteria or expertise of the prospective waiters recruited by the hotel in maintaining the reputation or good name of the hotel for the convenience of customers and to increase hotel turnover. However, there is no system or method applied by the hotel, in this case the Halay Tanjung Morawa hotel to support and facilitate the management in making decisions to determine prospective waiters in the recruitment carried out by the hotel.Analytical Hierarchy Process (AHP).with the use of the AHP method can produce good and effective decisions in recommending the best waiters according to the highest score, which is rank 1, so that the existence of a decision support system with the application of this AHP method can assist hotel management in recruiting their waiters for each episode objectively.